Antimicrobial Activity and HPLC Fingerprinting of Crude Ocimum Extracts - S. S. Deo; F. Inam; R. P. Mahashabde (E-Journal of Chemistry)
The antimicrobial activity of crude methanolic and aqueous extracts of Ocimum sanctum and Ocimum kilimandsacharicum against gram positive, gram negative and antifungal activity was evaluated to find the zone of inhibition and to set a HPLC profile or fingerprint of these extracts. The crude methanolic extract of Ocimum sanctum showed strong antimicrobial activity against S.aureus and C. albicans and moderate activity against E. coli and B. subtilis. The crude methanolic extract of Ocimum kilimandsacharicum showed strong antimicrobial activity against S. aureus, E. coli and C. albicans at higher concentration, same as that shown by the standard for C. albicans. It showed moderate activity against B. subtilis. The crude aqueous extracts of Ocimum sanctum showed strong antimicrobial activity against S.aureus and moderate against others. Whereas the crude aqueous extracts of Ocimum kilimandsacharicum showed moderate activity against the gram positive and gram negative organisms and strong activity against C. albicans at higher concentration, same as that shown by the standard for C. albicans.